2020
DOI: 10.3389/fcell.2020.00333
|View full text |Cite
|
Sign up to set email alerts
|

Regional Injection of CAR-T Cells for the Treatment of Refractory and Recurrent Diffuse Large B Cell Lymphoma: A Case Report

Abstract: Background: Lymphoma is a common hematological malignancy with many subtypes and considerable heterogeneity. Traditional treatments include chemotherapy, radiotherapy, and surgery. Patients with relapsed, refractory or advanced stage lymphoma have a dismal prognosis. In recent years, chimeric antigen receptors (CARs) have been recognized as powerful tools that redirect antigen-specific T cells independent of human lymphocyte antigen (HLA) restriction and specifically kill tumor cells. Satisfactory results with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…(C) Body weight curve of mice avoiding systematic targeting of T cells in normal tissue, further reducing the risk of unnecessary toxicity. 28,29 Moreover, we also found that the systematic delivery of 5T4 CAR-T cells in the subcutaneous injection xenotransplanted model significantly controlled the growth of Skov3 ovarian cancer. Tumor regression quickly appeared 2 weeks after CAR-T cells delivery by tail vein injection.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…(C) Body weight curve of mice avoiding systematic targeting of T cells in normal tissue, further reducing the risk of unnecessary toxicity. 28,29 Moreover, we also found that the systematic delivery of 5T4 CAR-T cells in the subcutaneous injection xenotransplanted model significantly controlled the growth of Skov3 ovarian cancer. Tumor regression quickly appeared 2 weeks after CAR-T cells delivery by tail vein injection.…”
Section: Discussionmentioning
confidence: 61%
“…delivery shows better curative effect due to it subtly avoids transport restrictions, effectively redistributing 5T4 CAR‐T cells to tumor sites, potentially reducing their systemic distribution, and avoiding systematic targeting of T cells in normal tissue, further reducing the risk of unnecessary toxicity. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…One method that has become a common practice in CAR T-cell testing in animal models and clinical trials is injection of CAR T cells into the tumor rather than intravenous delivery. Some improvement of CAR T-cell homing and infiltration in solid tumors has been seen, but it has not shown a complete fix of the problem [ 87 , 88 ].…”
Section: Effects Of the Immunosuppressive Tme On Car T Cellsmentioning
confidence: 99%
“…Although the targeted antigen can be expressed in normal tissues, resulting in inadvertent immune-related damage, accumulation of CAR T cells has shown promising tumor eradication in several tissues such as liver, lymph nodes, and bone marrows. [144][145][146] CAR T cell therapy is sometimes combined with chemotherapy or low-dose irradiation regimens that would reduce levels of immuno-suppressive cells (e.g., T regulatory cells, myeloid cells) and increase the likelihood of CAR T cell survival. Brentjens et al 147,148 have experimentally discovered this controversial observation from patients with chemotherapy-refractory chronic lymphocytic leukemia (CLL) or relapsed B cell ALL.…”
Section: Immunoconjugatesmentioning
confidence: 99%